NEW WAY OF DEFINITION OF OPTIMUM FREQUENCY ROTATION THE CANS AT ROTATIONAL THERMAL STERILIZATION - M. M. Achmedov; A. F. Demirova; M. M. Achmedova; K. R. Gammatcaev; T. N. Daudova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In work results of researches on development of a new way of determination of optimum frequency of rotation of cans at rotational sterilization are presented.Optimum frequencies of rotation for various product range are specified in various banks. It is established that the optimum speed of rotation of cans can be determined on the maximum speed of heating of a product in the least warmed up point.